2023
DOI: 10.1111/jmg.12706
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic and chronological constraints on the early Paleozoic tectono‐thermal evolution of the Olkhon Terrane, southern Siberia

Abstract: Terranes accreted to the southeastern margin of the Siberian Craton record an important early Paleozoic tectono-thermal event (known as the Baikal orogenic cycle) in the evolution of the Central Asian Orogenic Belt (CAOB). However, the precise metamorphic conditions and relative timing of this event and its linkage to the wider CAOB remain far poorly constrained. The best exposed of these terranes is the Olkhon Terrane on the western bank of Lake Baikal.Here, late Neoproterozoic through early Paleozoic island … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 100 publications
3
16
0
Order By: Relevance
“…However, in some places the hinges of Fu 3 folds show steep plunges to the NE or SW which may imply moderate to steep dip of Sh 1 MIG prior to Fu 3 folding (Figure 5a). Our previous study (Z. Y. Li et al., 2023) revealed that the metamorphic cycle associated with the development of the Sh 1 MIG reached the P max at 8 kbar at 770°C and was followed by a second phase of HT ‐ low pressure (LP) metamorphism marked by M2 re‐equilibration at around 4 kbar and 700°C. The structures related to this event are widely discussed and will be assigned as D 2 MIG .…”
Section: Principal Tectono‐metamorphic Features Of the Olkhon Terranementioning
confidence: 98%
See 4 more Smart Citations
“…However, in some places the hinges of Fu 3 folds show steep plunges to the NE or SW which may imply moderate to steep dip of Sh 1 MIG prior to Fu 3 folding (Figure 5a). Our previous study (Z. Y. Li et al., 2023) revealed that the metamorphic cycle associated with the development of the Sh 1 MIG reached the P max at 8 kbar at 770°C and was followed by a second phase of HT ‐ low pressure (LP) metamorphism marked by M2 re‐equilibration at around 4 kbar and 700°C. The structures related to this event are widely discussed and will be assigned as D 2 MIG .…”
Section: Principal Tectono‐metamorphic Features Of the Olkhon Terranementioning
confidence: 98%
“…The Chernorud Zone is characterized by mafic garnet‐ clinopyroxene‐amphibole bearing granulite and intermediate to felsic granulite mainly consisting of garnet, clinopyroxene, orthopyroxene, plagioclase, K‐feldspar, and quartz (Z. Y. Li et al., 2023). Apart from the mafic and felsic granulite, the Chernorud Zone contains numerous highly elongated layers of marble and quartzite that are together with felsic granulite wrapped around mafic and ultra‐mafic lenses and boudins (Fedorovsky & Sklyarov, 2015).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations